Life's solution : inevitable humans in a lonely universe - Conway Morris, S. (Simon) (Cambridge University Press, 2003)
The eminent evolutionary palaeobiologist Simon Conway Morris challenges the accepted view that if the tape of life were wound back, the replay would be very different. He also asks: are we alone?